2008
DOI: 10.1001/archinternmed.2007.123
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Plus Progestin and Breast Cancer Detection by Means of Mammography and Breast Biopsy

Abstract: clinicaltrials.gov Identifier: NCT00000611.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 48 publications
1
70
0
2
Order By: Relevance
“…(Table 1). Second, the stable trends in incidence rates may reflect improved sensitivity of mammography without influence of HT, as HT increases breast density (16) and compromises the diagnostic performance of mammograms and breast biopsies (17). It may also in part reflect the relatively stable rates of screening mammography in the United States since 2000 (18).…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1). Second, the stable trends in incidence rates may reflect improved sensitivity of mammography without influence of HT, as HT increases breast density (16) and compromises the diagnostic performance of mammograms and breast biopsies (17). It may also in part reflect the relatively stable rates of screening mammography in the United States since 2000 (18).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Now with longer follow-up, there remains a cumulative, statistically significant increase in breast cancers in the combined hormone therapy group and the cancers more commonly had lymph node involvement. The observed adverse influence on breast cancer mortality with combined hormone therapy can reasonably be explained by the influence on breast cancer incidence and stage.…”
Section: Discussionmentioning
confidence: 99%
“…1 Combined hormone therapy increased invasive breast cancers 1, 2 and delayed breast cancer diagnoses resulting in more advanced stage. 2,3 Recently, when examined after 7.9 years (1.4) mean (SD) follow-up, the breast cancer risk associated with combined hormone therapy declined soon after discontinuation of hormones. 4 Nonetheless, questions of clinical relevance remain, including the cumulative, long term effect of estrogen plus progestin on breast cancer incidence and, whether breast cancer mortality is increased by combined hormone therapy use.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that prolonged use of combination HRT (estrogen and progesterone) increases the risk of breast cancer, as well as the risk of being diagnosed with advanced disease [185,186]. Findings from the current study indicated that breast cancer patients who reported HRT or OCP use before breast cancer diagnosis were less likely to be diagnosed at an advanced stage of disease.…”
Section: Discussionmentioning
confidence: 50%
“…However, due to the limited range of individual-specific variables available in the dataset, some previously identified individual risk factors for an advanced breast cancer at diagnosis were unexamined. Obesity, menopausal status, and smoking behaviour are individual factors associated with advanced breast cancer at diagnosis, and are more common among the rural Australian population [69,77,78,[183][184][185][186]]. These additional individual-level risk factors are not available in cancer registry datasets.…”
Section: Chapter Aimsmentioning
confidence: 99%